Model of the Research Master Program: Results of Testing the New Modules of Basic Educational Programs in the Moscow City Teacher Training University - Vesmanov S.V.; Vesmanov D.S.; Akopyan G.A.; Istochnikov V.V.; Shevchenko P.V. (Psihologiceskaâ nauka i obrazovanie (2007), 2015)
The article describes the results of testing new modules of basic educational master programs at the Moscow City Teacher Training University. The authors present quantitative and qualitative test characteristics of the modules of research master program, the formation of competencies as units of meaningful activities. The additions to working curricula of disciplines, practices and research were lit in the form of specified learning outcomes in four groups of competencies developed in the framework in the research master’s. The changes in the Federal State Educational Standard for Higher Education of the training direction # 44.04.01 «Pedagogical education» and «Order of organization and implementation of educational activity on bachelor, specialty, and master educational programs of higher education» are proposed. According to the testing results authors carried out correction of new modules of the research master's and a number of the measures directed on increase of efficiency educational programs implemented in the research master’s